Palaeogeographical conditions of the functioning of the fossil channel in the Koźmin-Głowy site; Warta River valley, Koło Basin - Petera-Zganiacz, Joanna; Majecka , Aleksanda; Dzieduszyńska , Danuta; Forysiak , Jacek; Okupny , Daniel; Skoczylas-Śniaz, Sylwia; Stachowicz-Rybka, Renata; Twardy, Juliusz; Zawiska, Izabela (Acta Geographica Lodziensia, 2024)
The article presents environmental changes recorded in sediments filling the fossil channel in the Warta River valley. Basic sedimentological analysis, pollen analysis, plant macrofossils, Cladocera and geochemical analysis were carried out, and the age of the sediments was determined using the radiocarbon method. The research results allowed a determination of the onset of the palaeochannel’s infilling with organic sediments to the Older Dryas, and its completion in the Preboreal period. The oxbow lake was influenced by fluvial processes, which were particularly intense during the Older Dryas and the Younger Dryas/Preboreal transition. Later, the flow in the channel was activated, the channel meandered, with strong aggradational tendencies.